Sustainable science learning model integrated with indigenous values to promote climate change prevention among prospective science teachers - Parmin Parmin; Muhammad Abdul Jabbar; Eli Trisnowati (LPMPP Universitas Negeri Yogyakarta, 2026)
Science learning in schools plays a strategic role in advancing the achievement of the Sustainable Development Goals (SDGs) in Indonesia. SDG 13 addresses climate change, integrated with SDG 4 through the provision of quality education. Instilling a lifestyle of climate change prevention will enhance harmony with the environment. The purpose of this study was to measure the impact of a sustainable science learning model integrated with the indigenous values of prospective science teachers to instill a lifestyle of climate change prevention. The research method used was a mix of quantitative and qualitative methods, collecting quantitative data on the impact of a climate change prevention lifestyle and qualitative data on prospective teachers' abilities to prepare climate change prevention lessons. Results obtained above a score of 4.00 indicate that it has a real impact on prospective teachers' climate change prevention activities. The ability of prospective teachers to prepare lessons, with an average result of 4.22, indicates it is in the good category. The sustainable science learning model, integrated with the indigenous values of prospective science teachers, has a real impact on instilling a lifestyle of climate change prevention.